PENERAPAN STANDAR PROSES DALAM MANAJEMEN PEMBELAJARAN DI SMP NEGERI 6 KOTA MAKASSAR - Nirmaladewi, Nirmaladewi (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2017)
The study aimed at discovering (i) the implementation of process standard in school management at SMPN 6 in Makassar, (ii) the supporting and inhibiting factors in establishing process standard in school management at SMPN 6 in Makassar, and (iii) the implication of the implementation of process standard in school management at SMPN 6 in Makassar. The study employed qualitative approach. Data were collected through observation, interview, and documentation. The result of the study revealed that (i) the process standard was implemented by conducting well managed administration. The learning process was conducted in well planned and systematic program based on the lesson plan, (ii) the supporting factors of the implementation of process standard was equal to the inhiting factor both internally and externally. The two factors were intracted and gave influence on objective achievement of the school, and (iii) the implementation of process standard gave implication for the improvement of teacher professionalism and learning achievement of students both academically and non-academically.